The Influence of Brand Equity and Product Quality on Houses Purchase Decisions in Bukit Cimanggu City Residents: - - Kris Banarto (Journal of Business, Management, & Accounting, 2022)
Effects of Brand Equity and Product Quality Against Buying Decision of Houses in Bukit Cimanggu City Bogor Residents. The research was done by taking the respondents from the buyer at the same time as the residents in the Bukit Cimanggu City Bogor, marketing approaches, in particular, to explore and analyze the influence of brand equity and product quality on the decision of buying a house in Bukit Cimanggu City Bogor. Research data analysis is done using statistical and quantitative analysis descriptive, prime data obtained from the results of empirical research through questionnaires. The sample size in this study was 100 people, drawn to a simple random sample drawn in a way, and as many as 20 people to test the instrument. The results showed that the influence of brand equity on purchase decisions was 19.1%, the effect of the decision of purchasing the product quality by 58.2%, and is jointly brand equity and product quality influence purchase decisions by 67.4%.